1984
DOI: 10.1111/j.1365-2672.1984.tb04700.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a cup scrub technique for quantification of the microbial flora on bovine skin

Abstract: A cup-scrub technique devised for sampling the human skin surface microflora was evaluated in cattle. Scrub samples from bovine skin contained clumps of squama and bacterial microcolonies which were progressively broken down by shaking. This was accelerated in the presence of ballotini beads but aggregations of bacteria were still present after prolonged agitation. Vigorous shaking, particularly with beads, decreased the viability of the bacteria and optimum viable counts were obtained after manual shaking for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…and Corynebacterium spp. (Lloyd, 1984;White et al, 1989). More comprehensive studies by Woodward et al (1988) and Cullen & Hebert (1967) also reported the less frequent isolation of Acinetobacter spp., Aerococcus spp., Bacillus spp.…”
Section: Discussionmentioning
confidence: 92%
“…and Corynebacterium spp. (Lloyd, 1984;White et al, 1989). More comprehensive studies by Woodward et al (1988) and Cullen & Hebert (1967) also reported the less frequent isolation of Acinetobacter spp., Aerococcus spp., Bacillus spp.…”
Section: Discussionmentioning
confidence: 92%
“…Glove-based sampling is preferred when characterization of the resident population is desired, while swab-based sampling may be appropriate for some studies aimed at assessing only a portion of the hand surface area when transient bacterial populations are the focus of the study. The cup scrub sampling technique (42) could be explored in future studies, as it may be a more direct comparison to swabbing, as it can also be done on smaller areas of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published research pertaining to apocrine secretion and its major components has utilized pure apocrine secretion collected via epinephrine‐induced secretion [12]. The cup‐scrub skin sampling method has been utilized for the collection of bacteria from skin and to document the deposition of personal care products on skin [16, 17]. Hence, presented here is a well‐accepted, non‐invasive skin sampling method that can be used to detect and quantify epidermally secreted apocrine proteins.…”
Section: Discussionmentioning
confidence: 99%